Sztuka pisania – sztuka czytania. Edukacja literacka na uniwersytecie i w życiu kulturalnym - Jaworski, Marcin (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The article discusses the teaching of creative writing at the university and within literary and cultural life, using as its case study the development at Adam Mickiewicz University in Poznań of the artistic-literary specialisation established in 2007 and the degree programme Creative Writing introduced in 2020. It draws attention to the still developing position of creative writing among the disciplines of the humanities, a position that calls for clearer definition, as well as to its place between academic education and the institutions and participants of literary and cultural life beyond the university – a relationship that deserves further support and development. An important element of artistic education is the combination of workshop-based classes with philological courses, in which the art of interpretation plays a central role. Interpretation is understood here as a practice that brings together skills of literary analysis and the practical craft of writing, supporting students in developing both interpretive competence and a growing awareness of literature as a cultural practice.